Diagnostic pitfalls in computed tomography of the chest. (February 2023) - Patiño, Paula; Semionov, Alexandre; Sayegh, Karl; Kosiuk, John; Pressacco, Josephine
Anatomical variants and imaging artifacts on thoracic computed tomography (CT), when unrecognized as such, can lead to radiological misinterpretation and erroneous diagnosis. This is a concise review of 15 common CT diagnostic pitfalls due to anatomical variants and imaging artifacts which have potential to be misinterpreted as significant pathology, such as neoplasia, infection, traumatic injury, interstitial lung disease, pleural disease, or vascular lesions.